Prenatal Exposure to P[M.sub.2.5] Oxidative Potential and Lung Function in Infants and Preschool-Age Children: A Prospective Study - Marsal, Anouk; Slama, Remy; Lyon-Caen, Sarah; Borlaza, Lucille Joanna S; Jaffrezo, Jean-Luc; Boudier, Anne; Darfeuil, Sophie; Elazzouzi, Rhabira; Gioria, Yoann; Lepeule, Johanna; Chartier, Ryan; Pin, Isabelle; et al. (Environmental health perspectives, 2023)
Background: Fine particulate matter (P[M.sub.2.5]) has been found to be detrimental to respiratory health of children, but few studies have examined the effects of prenatal P[M.sub.2.5] oxidative potential (OP) on lung function in infants and preschool children. Objectives: We estimated the associations of personal exposure to P[M.sub.2.5] and OP during pregnancy on offspring objective lung function parameters and compared the strengths of associations between both exposure metrics. Methods: We used data from 356 mother-child pairs from the SEPAGES cohort. PM filters collected twice during a week were analyzed for OP, using the dithiothreitol (DTT) and the ascorbic acid (AA) assays, quantifying the exposure of each pregnant woman. Lung function was assessed with tidal breathing analysis (TBFVL) and nitrogen multiple-breath washout ([N.sub.2]MBW) test, performed at 6 wk, and airwave oscillometry (AOS) performed at 3 y. Associations of prenatal P[M.sub.2.5] mass and OP with lung function parameters were estimated using multiple linear regressions. Results: In neonates, an interquartile (IQR) increase in O[P.sup.DTT.sub.v] (0.89 nmol/min/[m.sup.3]) was associated with a decrease in functional residual capacity (FRC) measured by [N.sub.2]MBW [[beta] = -2.26 mL; 95% confidence interval (CI): -4.68, 0.15]. Associations with P[M.sub.2.5] showed similar patterns in comparison with O[P.sup.DTT.sub.v] but of smaller magnitude. Lung clearance index (LCI) and TBFVL parameters did not show any clear association with the exposures considered. At 3 y, increased frequency-dependent resistance of the lungs ([Rrs.sub.7-19]) from AOS tended to be associated with higher O[P.sup.DTT.sub.v] ([beta] = 0.09hPa * s/L; 95% CI: -0.06, 0.24) and O[P.sup.AA.sub.v] (IQR = 1.14nmol/min/[m.sup.3]; [beta] = 0.12hPa * s/L; 95% CI: -0.04, 0.27) but not with P[M.sub.2.5] (IQR = 6.9 [micro]g/[m.sup.3]; [beta] = 0.02hPa * s/L; 95% CI: -0.13, 0.16). Results for FRC and [Rrs.sub.7-19] remained similar in OP models adjusted on P[M.sub.2.5]. Discussion: Prenatal exposure to O[P.sup.DTT.sub.v] was associated with several offspring lung function parameters over time, all related to lung volumes.